Answer:
f(x-7) = x -12
Step-by-step explanation:
horizontal translation 7 units right: f(x-7)
f(x) = x - 5
f(x-7) = x-7 -5 = x -12
Distance formula
D = √((x1 - x2)2 + (y1 - y2)2) We have three distances that we are dealing with. Between the Theater and the Park, between the Theater and the Pier, and between the Park and the pier. In both routes we have to go between the Theater and the Park. The distance between those is the same regardless of which way we go, so we can ignore doing the math for that. That leaves us two distances. Let's plug them in. Theater to PierD = √((0 - 10)2 + (3 - 9)2) = √(100 + 36) ≈ 11.6619 Park to PierD = √((2 - 10)2 + (1 - 9)2) = √(64 + 64) ≈ 11.3137 11.3 < 11.7
the answer to your equation is
n=40
Step-by-step explanation:
It cannot be (4, -3) as there would be 2 outputs (3 and -3) for the input 4, therefore it becomes a one-to-many relationship and not a function.
Answer:
michelle is 23 inches shorter than her dad
Step-by-step explanation: